'Is there such thing as evil objects?': A Review of Lucius Burckhardt Writings: Lucius Burckhardt Writings: Rethinking Man-Made Environments. Politics, Landscape & Design, Jesko Fezer and Martin Schmitz (eds.), Vienna: Springer, 288 pages, 2012, ISBN: 9783709112564. Issue 1 (11th April 2014) - Förster, Kim
Abstract : Since the death of Lucius Burckhardt in 2003, his work has been discovered as an alternative position in architecture and planning in the German-speaking world. This volume for the first time compiles 24 'best of' texts on such topics as politics, landscape, and design, written between 1957 and 1999, in an English translation, including a valuable introduction by the editors.